Papain-like protease of SARS-CoV-2 inhibits RLR signaling in a deubiquitination-dependent and deubiquitination-independent manner - Ran, Xiang-Hong; Zhu, Jia-Wu; Chen, Ya-Yun; Ni, Run-Ze; Mu, Dan (Frontiers in Immunology, 2022)
The newly emerged severe acute respiratory syndrome (SARS) coronavirus-2 (SARS-CoV-2) can result in dysregulated interferon (IFN) responses that contribute to disease severity. The papain-like protease of SARS-CoV-2 (SCoV2-PLpro) has been previously reported to attenuate IFN responses, but the underlying mechanism is not fully understood. In this study, we found that SCoV2-PLpro potently suppressed IFN production and signaling induced by Sendai virus as well as RIG-I-like receptor (RLR) signaling pathway components, including RIG-I, MAVS, TBK1, TRAF3, TRAF6, and IRF3. SCoV2-PLpro exhibited different specificity and efficiency than SARS-CoV PLpro, with the former exerting a greater inhibitory effect on the RIG-I- and TRAF3-mediated IFN response but a weaker effect on the MAVS-mediated IFN response. Furthermore, we showed that SCoV2-PLpro significantly reduced K63-ubiquitination of RIG-I, MAVS, TBK1, TRAF3, TRAF6, and IRF3 and K48-ubiquitination of IκBα, which are known critical for the innate immune signal transduction. The deubiquitinating (DUB) activity of SCoV2-PLpro required a catalytic residue cysteine 111 (C111) but not the UBL domain. Notably, by utilizing the DUB-defective C111 mutant, we demonstrated that SCoV2-PLpro targeted RLR signaling pathway regulators via deubiquitination-dependent and -independent mechanisms, with the inhibitory activities of RIG-I and TBK1 correlating with DUB function, whereas the antagonism effects on MAVS, TRAF3, TRAF6, and IRF3 independent on DUB activity. Overall, our results reveal that SCoV2-PLpro evolves differential IFN antagonism activity from SCoV1-PLpro and it targets multiple key RLR signaling pathway components via various mechanisms, providing insights into SARS-CoV-2 pathogenesis and clues for developing antiviral therapies for COVID-19.